EU Food Law Handbook - Meulen, Bernd Van der, (European Institute for Food Law series ;, 2020)
The twenty-first century has witnessed a fundamental reform of food law in the European Union, to the point where modern EU food law has now come of age. This 'EU Food Law Handbook' presents the most significant elements of these legal developments with contributions from a highly qualified international team of academics and practitioners. Their analysis is based on a shared vision of the structure and content of EU food law. The book takes the perspective of food law embedded within general EU law. It highlights the consequences of this combination and provides insights into both substantive and procedural food law. Taking the General Food Law as a focal point, this handbook systematically analyses and explains the institutional, substantive and procedural elements of EU food law. Principles are discussed as well as specific rules addressing food as a product, the processes related to food and communication about food to consumers through labelling. These rules define requirements on subjects like market authorisation for food additives, novel foods and genetically modified foods, chemical and biological contaminants in food, food hygiene, tracking & tracing, withdrawal & recall, food labelling and claims. The powers of public authorities to enforce food law and to deal with incidents are outlined. Attention is given to the international context (WTO, Codex Alimentarius) as well as to private standards. In addition to the systematic analysis, the book includes selected topics such as nutrition and health policy, special foods, food import requirements, food contact materials, intellectual property, private food law, and animal feed. In this new edition, existing chapters have been updated to take account of many important developments in legislation and case law. Several new topics have been added to the analysis such as the right to food, organics and food fraud. The 'EU Food Law Handbook' is produced in co-operation with the European Institute for Food Law. It is relevant for practitioners and academics both with and without a background in law. It is ideal for education purposes.